Relationship among halal traceability system adoption, halal industry environmental factors and halal food supply chain performance - Ab Rashid, Norasekin (2016)
Halal has become one of the features being discussed especially in food production either in Muslim countries or non-Muslim countries due to the increasing demand from customers worldwide. The increase number of cases on the misuse of Halal logo and quest ionable status of Halal food has raised many concerns among the Muslim consumers regarding the status of Halal food in Malaysia. The various reports on the issues of fraudulent cases and physical contaminat ion in Halal food also indicate that there are weaknesses in the procedure of determining Halal food. In this case, food companies must be prepared to implement systematic traceabilit y system to ensure the authenticity of Halal products and comprehend the importance of Halal industry environmental factors in enhancing integrity of Halal food supply chain and performance. Accordingly, the main purpose of this study is to examine the relat ionship between the Halal traceability system adoption and Halal industry environmental factors on Halal food supply chain integrity and performance. Using a quant itative research approach, survey questionnaires were distributed to 176 Malaysian Halal food and beverages companies through mail and during Halal exhibit ion (i.e., MIHAS and HALFEST). Partial Least Squares (PLS) software was applied to examine the direct and mediating effect hypotheses. The results revealed that Halal industry environmental factors have a relat ionship with Halal traceabilit y system adoption. Moreover Halal traceability system adoption and Halal industry environmental factors were significant ly and positively related to the importance of Halal food supply chain integrity. Furthermore, the findings also show that Halal traceability system adoption and Halal food supply chain integrity have significant relat ionship on Halal food supply chain performance. However, Halal industry environmental factors were not perceived as important in determining the Halal food supply chain performance. The study also found a partial role of Halal food supply chain integrity in mediat ing the relat ionship between Halal traceability system adoption and Halal food supply chain performance.